Studying the Effect of Changes in Dew Point Temperature on Extreme Precipitation in the North West of Iran - Mahnaz Rostamian; Seyed Hossein Mirmousavi; Kohzad Raispour (Nīvār)
In the present research, using the daily precipitation data of 479 meteorological and rain gauge stations in the north west of Iran, the relationship between the changes in the dew point temperature and the precipitation in this region was investigated. For this purpose, the Classification and Regression Trees method was used to determine the effective temperature class in the extreme precipitations and the geographical weighted regression was used to identify the significant areas. The results of this research showed that there is a direct and significant relationship between these two variables and with the increase in the dew point temperature, the intensity of the extreme precipitation also increases in the 90th, 95th and 99th percentiles. The results of the Classification and Regression Trees showed that different dew temperatures (low and high values) both play a role in the occurrence of extreme precipitation in the North West of Iran, but in very intense extreme precipitation (precipitation above the 99th percentile), the role of high dew temperatures is greater than low values. Also, the southwestern part of the studied area has the highest degree of correlation compared to other parts. This section corresponds to the areas that have the most precipitation. This shows that extreme precipitation affected by the dew point temperature occur in areas where the frequency of rain is high and the probability of flooding caused by this type of precipitation is also higher in this section than in other sections.